Giant inguinal hernia in a preterm child - Technical challenges and long-term outcome - Lauri Kauhanen; Tarja Iber; Topi T Luoto (Elsevier, 2022)
Giant inguinal hernias are rare in children, and they represent a unique challenge for pediatric surgeons. The sparse literature includes variable definitions of the disease and different surgical techniques without significant difficulties with the decrease of abdominal domain. We present a prematurely born boy with a unilateral giant inguinal hernia which developed promptly after birth. This case highlights the multiple possible challenges related to giant inguinal hernias in children. We also discuss the possible treatment options and the advantages and disadvantages based on the current literature.